2022
DOI: 10.1093/texcom/tgac033
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical connectivity and coupling of infraslow oscillation in the resting human brain: a 2-channel broadband NIRS study

Abstract: The resting-state infra-slow oscillation (ISO) of the cerebral cortex reflects the neurophysiological state of the human brain. ISO results from distinct vasomotion with endogenic (E), neurogenic (N), and myogenic (M) frequency bands. Quantification of prefrontal ISO in cortical haemodynamics and metabolism in the resting human brain may facilitate the identification of objective features characteristic of certain brain disorders. The goal of this study was to explore and quantify the prefrontal ISO of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(68 citation statements)
references
References 82 publications
1
67
0
Order By: Relevance
“…These metrics are (1) bilateral hemodynamic (i.e., Δ[HbO]) connectivity (bCONHbO), (2) bilateral metabolic (i.e., Δ[CCO]) connectivity (bCONCCO), (3) unilateral hemodynamic-metabolic coupling (uCOP) on the left, and (4) right side of the prefrontal cortex. In addition, we demonstrated that these constant and relatively reproducible metrics can be considered potential features of the human prefrontal cortex in young healthy adults 17 . We have also shown distinct alterations in these metrics across all three frequency bands in response to 1064-nm tPBM 16 …”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…These metrics are (1) bilateral hemodynamic (i.e., Δ[HbO]) connectivity (bCONHbO), (2) bilateral metabolic (i.e., Δ[CCO]) connectivity (bCONCCO), (3) unilateral hemodynamic-metabolic coupling (uCOP) on the left, and (4) right side of the prefrontal cortex. In addition, we demonstrated that these constant and relatively reproducible metrics can be considered potential features of the human prefrontal cortex in young healthy adults 17 . We have also shown distinct alterations in these metrics across all three frequency bands in response to 1064-nm tPBM 16 …”
Section: Introductionmentioning
confidence: 74%
“…In addition, disturbances in vasomotion have been associated with aging, neurological disorders, and other diseases such as atherosclerosis, 13 cardiovascular disease, 14 and Alzheimer’s disease 15 . In other studies published by our group, we have shown that vasomotion and its frequency-domain characteristics over the prefrontal cortex at rest can be quantified as brain activity features in healthy humans 16 , 17 …”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations